The ancient world of the mid-17th century Ukrainian poetry phraseology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article analyzes the specific phraseology of the ancient origin functioning in the Ukrainian poetic discourse of the 17th century. It is concluded that the main phraseology occurrence factor is the internal form of the proper name, which is used by the authors in order to make their works more expressive.
Keywords: poetic discourse; Ukrainian language of the 17th century; ancient mythology; idiom; semantics